Effect of Dietary Incorporation of Chili (Capsicum annuum) Leaf Powder on Production Performance and Egg Quality Parameters of Rhode Island Red Laying Hens - Abhilasha,; Mondal, B. C.; Kumar, Ripusudan; Palod, Jyoti; Huozha, Ruokuobeinuo; Kumar, Anil; Prasad, Srishtipriya; Ranwa, Suman (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present experiment was planned to ascertain the effect of dietary incorporation of chili (Capsicum annuum) leaf powder on production performance and egg quality parameters of Rhode Island Red laying hens of 28 weeks of age for a period of 12 weeks. Hens were individually weighed and then randomly assigned into four treatment groups with three replicates of 6 birds each viz., T1: (control, containing basal diet); T2: Incorporation of 0.5% chili leaf powder in basal diet; T3: Incorporation of 1.5% chili leaf powder in basal diet; T4: Incorporation of 2.5% chili leaf powder in basal diet. The results indicated that egg production and feed conversion ratio were not significantly affected. However, overall average feed intake significantly (P
Keywords: Chili leaf powder; Egg quality parameters; Production performance; Rhode Island Red laying hens